Evaluating key performance indicators of the process of care in juvenile idiopathic arthritis - Sarah M. Cooper; Gillian R. Currie; Seija Kromm; Marinka Twilt; Deborah A. Marshall (BMC, 2023)
Abstract Objective To determine whether and how often the information to measure a set of key performance indicators (KPIs) in juvenile idiopathic arthritis (JIA) is found in data collected routinely in a Pediatric Rheumatology Clinic. Methods A retrospective electronic chart review and administrative data analysis was conducted for a cohort of 140 patients with JIA at a tertiary Pediatric Rheumatology Clinic between 2016-2020. The set of KPIs include measuring patient outcomes (joint assessment, physician's global assessment of disease activity, assessment of functional ability, composite disease activity measurement), access to care (waiting time between referral and first visit, visit with the rheumatologist within the first year of diagnosis, annual follow-up visits with the rheumatologist), and safety (tuberculosis screening, and laboratory monitoring). Documentation was assessed as a binary variable indicating whether the required information was ever found. Documentation frequency for each KPI was assessed with counts and percentages of the number of times the required information was documented for each clinic visit. Compliance with the safety KPI definitions was assessed using administrative databases. Results Data for each KPI were found at least once in the cohort and documentation varied in frequency and consistency. Access to care and safety KPIs were documented more frequently than patient outcome KPIs. A joint assessment was documented at every visit for 95% of patients, 46% for an assessment of pain, and none for a physician's global assessment of disease activity, an assessment of functional ability, or a composite disease activity measurement. Conclusion Although feasible to measure, there is an opportunity for improving the consistency of documentation. Having an active system of monitoring KPIs and tools to simplify measurement is a key step in the process toward improved patient care outcomes. Streamlining the collection of KPI data can increase the likelihood of compliance. Next steps should involve replicating this study in various centres.